Usefulness of Infrared Thermal Imaging Camera for Screening of Postoperative Surgical Site Infection after the Nuss Procedure - Kenya Fujita; Masahiko Noguchi; Shunsuke Yuzuriha; Daisuke Yanagisawa; Kiyoshi Matsuo (Case Reports in Surgery)
Introduction and Objective. The Nuss procedure is widely used in the treatment of pectus excavatum worldwide. Postoperative pectus bar infection is one of the most serious complications associated with this procedure. Therefore, early detection of signs of implant infection is very important. However, this is difficult, and effective methods have yet to be established. Methods. We use a handheld infrared thermal imaging camera to screen patients for postoperative infection following the Nuss procedure. Here, we report a 28-year-old man with recurrent postoperative (Ravitch procedure) pectus excavatum. Results. Infrared thermography camera clearly indicated slight cellulitis in the right chest. Conclusion. Our technique may assist in preventing postoperative bar infection and removal caused by severe bar infection. Furthermore, this camera is potentially suitable for many situations in infection monitoring following subcutaneous implant surgery.